1995
DOI: 10.1002/mus.880181213
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of motor evoked potentials: Timing of jendrassik maneuver effects

Abstract: Remote voluntary contraction, such as the classical Jendrassik maneuver (JM), is a procedure routinely used to increase the amplitude of tendon reflexes in the lower limb. In 8 healthy subjects we studied the effects of JM on the motor evoked potentials (MEP) recorded from tibialis anterior muscle, produced by transcranial magnetic stimulation (stimulus output of 5-10% over motor threshold). In this study, JM consisted here of a bilateral violent handgrip, preceding magnetic stimulation from 100 to 50 ms (step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…In contrast, the response in H-reflex to mental arithmetic and remote contraction is inconsistent (Bussel et al, 1978;Gregory et al, 2001;Rossi-Durand, 2002;Zehr and Stein, 1999). Sensitization of the muscle spindle (Burg et al, 1974;Ribot-Ciscar et al, 2000;Rossi-Durand, 2002) and presynaptic disinhibition (Delwaide and Toulouse, 1980;Péréon et al, 1995;Zehr and Stein, 1999) are proposed to be involved in the modulations of stretch and H-reflexes during these tasks.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, the response in H-reflex to mental arithmetic and remote contraction is inconsistent (Bussel et al, 1978;Gregory et al, 2001;Rossi-Durand, 2002;Zehr and Stein, 1999). Sensitization of the muscle spindle (Burg et al, 1974;Ribot-Ciscar et al, 2000;Rossi-Durand, 2002) and presynaptic disinhibition (Delwaide and Toulouse, 1980;Péréon et al, 1995;Zehr and Stein, 1999) are proposed to be involved in the modulations of stretch and H-reflexes during these tasks.…”
Section: Introductionmentioning
confidence: 85%
“…The data were normalized to the mean value during the control period.tic disinhibition with the contraction of remote muscle(Gregory et al, 2001;Hultborn et al, 1987). Other groups observed presynaptic disinhibition(Delwaide and Toulouse, 1980;Péréon et al, 1995;Zehr and Stein, 1999), but it was only transient with the maximal…”
mentioning
confidence: 99%
“…Recently, MEPs in the upper and lower limb muscles following TMS were demonstrated to be facilitated during intense contraction of the remote muscle (Kawakita et al. , 1991; Péréon et al. , 1995; Muellbacher et al.…”
Section: Discussionmentioning
confidence: 99%
“…23 Evidence showed that a Jendrassik maneuver also increases MEP size in lower limb muscles. 24,25 Therefore, during stimulation of participants with motor complete SCI, to ensure maximum drive to spinal motoneurons, individuals were also asked at times to perform a Jendrassik maneuver, where they needed to clench their teeth and flex their fingers or arms bilaterally, into a hooklike form, with rest periods as needed. TMS stimuli were delivered at 4 second intervals (0.25Hz) at an intensity of 100% of the maximum stimulator output in SCI (single and paired pulse) and control (single pulse) subjects.…”
Section: Quadriceps Femoris Mepsmentioning
confidence: 99%